Cross‐lagged panel analysis of reciprocal effects of morphological processing and reading in Chinese in a multilingual context. (25th January 2018) - Zhang, Dongbo; Koda, Keiko; Leong, Che Kan; Pang, Elizabeth
Abstract : Background: While much is known about how morphological awareness (MA) contributes to reading development, little attention has been paid to how reading may conversely affect MA development, particularly in readers of Chinese in a bilingual/multilingual setting. Methods: The study adopted a cross‐lagged panel design. Young bilingual readers of Chinese were measured in MA, word reading and reading comprehension – all in Chinese – twice from Grade 3 to Grade 4. Results: Path analysis revealed that Grade 3 MA significantly predicted Grade 4 reading comprehension after controlling for the autoregressive effect. Over and above Grade 3 MA, Grade 3 reading also significantly predicted Grade 4 MA. Subsequent analyses, however, revealed disparate developmental patterns between those with Chinese and English, respectively, as their home language. Implications: These findings, while supporting reciprocity of developmental relationships between MA and reading, also suggested that the pattern of relationships can vary as a function of students' target language experiences in a bilingual/multilingual setting. Highlights: What is already known about this topic Morphological awareness predicts reading development in monolingual children, including Chinese‐speaking children. What this paper adds Morphological awareness predicts Chinese reading development in bilingual children with English as their primary reading language. There are developmentally reciprocal relationships between morphological awareness and reading abilities in those readers. The relationships vary in students with differential Chinese language experiences. Implications for theory, policy or practice Morphological awareness supports reading development but is also facilitated by reading experiences. Target language experiences moderate patterns of reading development. Morphological instruction may be particularly important for readers who do not speak the target language at home in a bilingual/multilingual setting.